They made me a criminal - Berkeley, Busby, 1895-1976; Garfield, John; Millhauser, Bertram, 1892-1958.; Dead End Kids (Group of actors); Warner Bros. Pictures (1923-1967); Cinetel Films ([Burbank, CA] : Warner Bros. Pictures, 1939)
A boxer's manager kills a reporter and then tries to blame the crime on his boxer, Johnnie. The manager dies in a car crash, but his body is mistaken for Johnnie's.
--
Based on a novel by Bertram Millhauser and Beulah Marie Hix.
John Garfield and the "Dead End Kids", Claude Rains, Ann Sheridan, May Robson, Gloria Dickson.
Photographer, James Wong Howe; editor, Jack Killiefer; music, Max Steiner.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Boxers (Sports) -- Drama; Fugitives from justice -- Drama; Boxing -- Drama; Ranches -- Arizona -- Drama; Boxing films; Crime films; Juvenile delinquency films; Film noir; Feature films; Film adaptations; Internet videos; Streaming video